Estratégias tecnológicas em transformação: um estudo da indústria farmacêutica brasileira - Santos, Maria Clara Bottino Gonçalves (2010)
The aim of this research is to examine the extension of changes on technological strategies of a group of Brazilian pharmaceutical companies, which we believe were induced by transformations in the institutional environment, occurred during the 1990s. We support that important institutional changes, as Patent‟s and Generic‟s Laws, have induced transformations on market insertion and competitive position of this companies and also have stimulated research and development efforts in Brazil. The research was based on the technology strategy and pharmaceutical industry literature and also on interviews with a group of Brazilian pharmaceutical companies, which are among the top companies in the pharmaceutical national rank and which, through a preview academic study, give us signals of growing efforts in technology activities and of inflections in their technological strategies. The research confirmed that the studied companies passed through a significant intensification of their technology efforts, but they are still above the global level and without big impact. In fact, the Brazilian pharmaceutical companies developed new drugs, as the Helleva of Cristália and the Acheflan of Aché. Besides that, almost all the studied companies are involved with innovative projects. However, the number of patents is still very low, what reflects the reduced capacity of patentable innovations. Indeed, a considerable share of their technology efforts is directed towards products which are not patentable, as generic drugs. Hence, most of the Brazilian pharmaceutical companies focus on brands and other commercial assets as an appropriability mechanism.